INNOVATIONS IN POLICY OF TEACHING AT THE UNIVERSITIES IN THE CONTEXT OF ACADEMIC REVOLUTIONS - Pivneva, L. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
Categories of the academic revolutions and innovations in a perspective of educational policy at the higher school are considered. Special attention is paid to the development of innovations in training at the foreign and Ukrainian universities, since X1X of a century up to now. It is noted that agricultural, industrial, global, demographic and other revolutions created basis for the academic revolutions which resulted from transformations of society and caused innovations in higher education systems. The contribution of the academic revolutions in strengthening of role of the universities in society is confirmed. The major innovations in training stimulated university teaching throughout all academic revolutionary periods (after 1867, 1945, 1983) in developed industrial and developing countries, such as the USA, some states of the European Union and Ukraine. Emergence of innovations in policy of teaching at the universities during the first academic revolution, their modification during the second one, and new turns in transformation of innovations during the third academic revolution is investigated. Introduction of innovations in teaching differed in intensity and scale during the academic revolutions. On examples of teaching it is shown how political and ideological processes in society influenced functioning of the universities. An attempt to compare educational processes during three revolutions and to reveal the most innovational period was made. It is proved that innovations in training were implanted in three academic revolutions, the third one turned out to be the most innovative. The major innovations in policy of teaching were connected with the development of scientific and technical knowledge that contributed to the emergence of the information society. The developed countries offered the introduction of policy of cooperation in the higher education that made impact on innovations in university education. The Coronavirus pandemic of 2019/20 demonstrated the need to use various forms of Internet communications (Zoom, Google Classroom, Moodle, Whereby, etc.) to switch to new opportunities to teach students in higher education institutions around the world at the beginning of the XXI century.